2014
DOI: 10.1016/j.toxrep.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Which exposure stage (gestation or lactation) is more vulnerable to atrazine toxicity? Studies on mouse dams and their pups

Abstract: Either during gestation or lactation, the experimental mouse dams received one of the following treatments: (a) diet free of pesticide; (b) diet enriched with atrazine (ATZ); 31.0 μg kg−1; (c) diet free of pesticide + oral vitamin E (α-tocopherol; 200 mg kg−1 per mouse); and (d) diet enriched with ATZ (31.0 μg kg−1) + oral vitamin E (200 mg kg−1 per mouse). At the weaning, pups and dams were killed and selected organs and blood samples were collected for analyses. Compared with the control results, ATZ induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…It is also known that, even at a nanomolar level, BPA is able to induce genotoxic, mutagenic, hepatotoxic, immunotoxic, neurotoxic, teratogenic, and carcinogenic effects [ 21 , 22 ]. More recently, it has been suggested that BPA increases the risk of obesity, diabetes, and heart disease in humans and is related to epigenetic modifications [ 9 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that, even at a nanomolar level, BPA is able to induce genotoxic, mutagenic, hepatotoxic, immunotoxic, neurotoxic, teratogenic, and carcinogenic effects [ 21 , 22 ]. More recently, it has been suggested that BPA increases the risk of obesity, diabetes, and heart disease in humans and is related to epigenetic modifications [ 9 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%